2017
DOI: 10.3390/ijerph14020125
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Refugees for Health Research: A Qualitative Study to Add Refugees’ Perspectives

Abstract: Research is needed to understand refugees’ health challenges and barriers to accessing health services during settlement. However, there are practical and ethical challenges for engaging refugees as participants. Despite this, there have been no studies to date specifically investigating refugee perspectives on factors affecting engagement in health research. Language-concordant focus groups in British Columbia, Canada, with four government-assisted refugee language groups (Farsi/Dari, Somali, Karen, Arabic) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…First, decisions made by community leaders and community members on whether to engage in research are impacted by a multitude of factors. Key determinants of research engagement by immigrant communities, based on this study as well as other studies reported in the literature, include safety concerns, affiliation of the researcher, nationality or gender of the researcher, financial incentives, lack of interest, mistrust, and concerns about privacy due to personally knowing the researcher (Dingoyan et al, 2012;Gabriel et al, 2017;Ruppenthal et al, 2005). These are all serious considerations that could impact a researcher's ability to recruit from such a community, even with the collaboration of community leaders.…”
Section: Methodological Experiencesmentioning
confidence: 55%
“…First, decisions made by community leaders and community members on whether to engage in research are impacted by a multitude of factors. Key determinants of research engagement by immigrant communities, based on this study as well as other studies reported in the literature, include safety concerns, affiliation of the researcher, nationality or gender of the researcher, financial incentives, lack of interest, mistrust, and concerns about privacy due to personally knowing the researcher (Dingoyan et al, 2012;Gabriel et al, 2017;Ruppenthal et al, 2005). These are all serious considerations that could impact a researcher's ability to recruit from such a community, even with the collaboration of community leaders.…”
Section: Methodological Experiencesmentioning
confidence: 55%
“…Out of nine individuals who were asked to take part in the study, eight agreed and the one declined for family reasons. The size of this sample is in line with the literature in this field, which indicates that, in conducting research with refugees, having small samples is relatively normal, as refugees are a difficult to reach, mobile population [ 76 , 77 ]. A small sample is also considered suitable for explorative studies, as the thoroughness of the close investigation enhances the validity of in-depth inquiry [ 78 ].…”
Section: Methodsmentioning
confidence: 62%
“…The rationale for undertaking a pilot trial of PM+ for AS&Rs, rather than proceeding to a full multicentre trial, is that there are several areas of uncertainty regarding trial viability. These include the feasibility of recruiting and retaining AS&Rs as study participants, the fidelity of intervention delivery, and the acceptability and utility of proposed study measures 30 . There may also be inequalities in mental health and wellbeing between AS&R groups, depending on their age, gender, nationality, education, occupational status, length of stay, access to resources and their current legal status in the UK which could inform the design of a full trial.…”
Section: Rationalementioning
confidence: 99%